Kfri... Kurdistan Battlefield - Ahmed, Dr. Kozad Mohammed (Sulaimani Journal for Humanities, 2025)
Kfri and its surrounding areas are the front lines of Kurdistan in terms of ethnicity, language and culture. The crack in this battlefield will have dangerous consequences for the identity of an important part of Kurdistan and increase the threat of its destruction. This study, which takes Kfri and its surrounding areas as an example, highlights the fundamental and important role that Kufri plays in maintaining the Kurdish stamp of South Kurdistan. To illustrate and prove these facts, a historical and archaeological comparison is made between the current role of the region and its role in two other historical periods, namely the Third Dynasty of Ur (last quarter of the third millennium BC) and the reign of Seymour (first quarter of the second millennium BC). In the first example, the collapse of the third dynasty of Ur in Hamrin, which led to the collapse of the empire at the hands of the Amorites and their allies, and then the delay of the Sumerian nation and even forgetting its existence for more than 3,800 years. He preserved the institution and identity of his country.